The Empowerment of Kembangan Utara Community in Increasing the Value of Soap Products Made from Waste Cooking Oil Through Visual Branding - Wardhani, Ariani Kusumo; Ulita, Novena; Malihah, Fadhila Dhia (Universitas Mercu Buana, 2025)
Waste Cooking Oil (WCO) is a prevalent form of household waste in Indonesia, often mismanaged due to a lack of awareness and infrastructure. In the densely populated area of RW 06 Kembangan Utara, Jakarta, improper waste disposal exacerbates environmental issues. However, repurposing WCO into soap offers renewed benefits and utility. Despite this, the association of the product with WCO creates a stigma that hinders its acceptance and economic viability. This community empowerment initiative aimed to address these challenges by enhancing the perceived value of soap products through visual branding strategies. Conducted over 12 sessions, the program engaged the RW 06 Kembangan Utara community in six systematic stages, providing education on WCO processing, product development, and branding. As a result, the community not only gained awareness about sustainable waste management but also acquired skills in creating visually appealing packaging to market their soap products effectively. The initiative serves as a foundation for fostering environmental responsibility and economic empowerment, encouraging the community to continue this small but impactful step toward a healthier and more sustainable future.